Antioxidant capacity of frozen Pleurotus ostreatus during convective drying - Valiente, Liliana; Ohaco Dominguez, Elizabeth Haydee; De Michelis, Antonio (Universidad de Puebla, México, 2018)
The influence of drying conditions on antiradical power, total phenols, flavonoids, and surface color in frozen basidiocarps of Pleurotus ostreatus was studied. Drying was carried out in an experimental rig, air velocity of 2 m/s, 5% relative humidity, and at different temperatures (50 C, 60 C, 70 C). Total phenols were determined according to the Folin-Ciocalteau method, flavonoids by complex formation with AlCl3 , and antiradical power by 1,1-diphenyl-2-picrylhydrazyl (DPPH). Surface color was also measured. A decrease was observed in the content of flavonoids during the first 15 min of drying in all temperatures tested. The content of total phenols increased, but subsequent stabilization was noted as drying progressed. Higher temperatures of the drying air preserved the antiradical power. A drying air temperature of 60 C was suitable for variables studied, showing P. ostreatus adequate stability of total phenols, antiradical power, and color. This process allows the use of oyster mushrooms out of season.